Management of Phytophthora Disease in black Pepper Nursery - Reshmy Vijayaraghavan (Department of Plant Pathology, College of Horticulture, 2003)
Phytophthora rot is the serious disease of black pepper nursery. An investigation was carried out to isolate and select the efficient antagonists from black pepper nurseries and use them alone or in combination with fungicides in the integrated management of the disease. The experiment was laid out at CCRP farm at College of Horticulture, Vellanikkara, The pathogen causing the disease was isolated and identified as Phytophthora capslcl Leonian emend A. Alizadeh and P.H.Tsao based on the cultural and morphological characters. Quantitative estimation of rhizosphere microflora from different pepper nurseries yielded more soil bacteria followed by fungi and actinornycetes. All the 22 fungi, five out of 20 bacteria and none of the actinomycetes tested were antagonistic to P. capsici. Among the fungal isolates, 13 isolates including standard culture of T. harzianum recorded cent per cent inhibition of P. capsici. Further, selection of the efficient isolates was carried out based on the antagonistic index (AI). The isolates 22 F and 34 F recorded an AI of3000 and 1500 respectively and these were identified as Trichoderma longibrachiatum and Trichoderma viride. The standard culture of T harzianum also recorded an AI of 1500. The three antagonists were found parasitic on Picapsici as evidenced by excessive coiling, penetration and disintegration of the hyphae. The fungicides viz., Bordeaux mixture, Kocide, Captaf and Kavach were incompatible with the three antagonists, while, lndofil M-45, Ridomil I\.1Z, Akomin and Anthracol were compatible. Fytolan showed partial compatibility with Tviride and 1~ harzianum but incompatible with T. longibrachiatum. Among the eight insecticides tested, Phorate and Carbofuran showed compatibility with the antagonists, whereas Monocrotophos, Quinalphos, Endosulfan, Dimethoate, Cypennethrin and higher concentration of Chlorpyrlphos were incompatible. In general, fertilizers like Urea, Rajphos, Ammonium sulphate and Muriate of potash (MoP) were compatible with antagonists, while, Factomphos and higher concentration of Urea did not support good growth.